The Meaning of Death for Adygs during the Years of the Caucasian War - Tekueva, Madina; Gugova, Marina; Nalchikova, Elena; Konovalov, Andrey (Journal of History Culture and Art Research, 2018)
The article deals with issues of everyday life of Adygs (Circassians) under conditions of a protracted military conflict during the Caucasian war in the first half of 19th century. Based on the recollections of eyewitnesses and direct participants in the events (Russian military officers and foreign observers), literary works of local authors and folklore sources, authors of the study explore a human factor in the history of the Caucasian War, in terms of emotions, dramatic experiences, fears, and transformation of ethnic consciousness. In this regard, histories of everyday life, gender history, and history of mentality appear to be the most productive research methods and approaches. Using related research tools allowed analyzing an inner perception of death of Adygs in the violent conflict. Adygs appear in the study not as a faceless side of the conflict, but as an active and personalized historical subject. The Caucasian war was not only a chain of political and war events, but was full of personal stories, tragedies of loss and sorrow, female experiences. The routine of death strengthened a respect for the dead, rebooting related symbolic content and ritual practices. At the same time, an erosion of the mental foundations of traditional culture occurs due to the fundamental changes in the conditions of prolonged war.